Banana peels as an alternative source of sugar production - Mohd Asyrak, Deraman (2012)
Carbohydrate is the main energy source of humans and animals. It is important for biosynthesis where it acts as precursor for most chemical reaction in our body. Carbohdydrate can be divided into four group which are polysaccharides, oligosaccharides, disaccharides, and monosaccharides. The latter two is commonly known as sugar. There are many foods high in carbohydrate include fruits, sweets, soft drinks, breads, pastas, beans, potatoes, bran, rice, and cereals. Most plants and fruits stored carbohydrate in form of starch. Banana for example contains high percentage of carbohydrate content. Detailed studies on chemical composition of banana peels also have shown high percentage of carbohydrate content. Thus, the large quantities of banana in Malaysia specifically, have the potential of being used industrially for production of sugars. It can alternatively become a new source of food sweetener and therefore reducing Malaysia's need on sugar cane for sugar production and also reduce our dependant on imported sugar. Besides, this study can help to eliminate environmental problems caused by banana waste. Experiment was set up to extract carbohydrate in form of starch from the banana peels by alkaline extraction method using 0.1 M NaOH. The confirmation of the extracts was done by microscopy images of starch granules. The microscopy images showed irregular shape of starch granules and when stained with iodine solution, the color changes from brown to deep blue. Further reaction takes place to convert starch into sugar in form of glucose syrup by enzyme hydrolysis using a-amylase and amyloglucosidase. Quantitative confirmation of total sugar syrup was done by Lane Eynon titration method and average result of five sample gives was 655.4 mg!lOOml or 0.33 % w/w.